겹꽃 분화용 할미꽃 신품종 ‘겨비’ - 이야성(Ya-Seong Lee); 김동관(Dong-Kwan Kim); 최덕수(Duck-Soo Choi); 최진경(Jin-Kyung Choi); 손동모(Dong-Mo Son); 최경주(Kyeong-Ju Choi); 백형진(Hyeong-Jin Baek); 임요섭(Yo-Sup Rim) (Korean journal of breeding, 2010)
할미꽃 신품종 ‘겨비’는 전라남도농업기술원에서 2001년에 자생 할미꽃(Pulsatilla koreana) 종자를 화학적 돌연변이를 유발(sodium azide 3 mM/16 hr)하고, 2004년과 2005년에 특성검정을 통해 2005년에 육성되었다. ‘겨비’의 꽃은 적자색이고 약은 진노랑, 주두는 적자색이며 화형은 겹꽃으로 꽃잎이 12매이다. 주당 화경은 6.3개, 화경장과 엽장은 각각 26.4, 14.2 cm이고, 화폭과 포폭은 각각 7.5, 11 A new pasqueflower (Pulsatilla koreana) variety, ‘Gyeobi,’ was derived from a mutation of native P. koreana at the Jeollanamdo Agricultural Research and Extension Services (JARES) in Naju, Korea. The ‘Gyoebi’ was obtained by treating seeds with 3 mM of a chemical mutagen, sodium azide, for 16 hr in 2001. The variety was established in 2005 after two years of selective breeding. ‘Gyeobi’ is characterized by reddish purple flowers with 12 double petals. The inherent characteristics of the variety are deep yellow anthers and reddish purple stigmas. The agronomic characteristics of the variety are 6.3 flowers per plant, 26.4 cm in flower height, 14.2 cm in leaf length, 7.5 cm in flower width, and 11.0 cm in bract width.